Assessment of Myocardial Collateral Blood Flow with Contrast Echocardiography - Kaul, Sanjiv (Korean Circ J, 2015)
Humans have pre-formed collateral vessels that enlarge with ischemia. In addition, new vessels can be formed within ischemic zones from pre-formed endocardial arcades of vessels providing rich collateral flow. Collateral flow under resting conditions (if >25% of normal) is enough to maintain myocardial viability, but may be insufficient to prevent myocardial ischemia under stress. Coronary angiography is a poor tool for collateral flow assessment. Myocardial contrast echocardiography is arguably the gold standard for experimental and clinical measurement of collateral flow. This review describes several experimental and clinical studies that highlight the importance of the collateral circulation in coronary artery disease.